Wavevector- and frequency-dependent shear viscosity of water: the modified collective mode approach and molecular dynamics calculations - Omelyan, I.P.; Mryglod, I.M.; Tokarchuk, M.V. (Condensed Matter Physics, 2005)
The transverse momentum time autocorrelation functions and wavevectorand frequency-dependent shear viscosity are calculated for an interaction site model of water using a modified collective mode approach and molecular dynamics simulations. The modified mode approach is based on a formulation which consistently takes into account non-Markovian effects into the kinetic memory kernels. As is demonstrated by comparing the theory results with the molecular dynamics data, the entire frequency dependence of the shear viscosity can be reproduced quantitatively over the whole wavelength range in terms of six generalized collective modes employing the kinetic memory kernel in the non-Markovian approximation of the third order. It is also shown that the results corresponding to the exact atomic and abbreviated molecular descriptions may differ considerably. In the infinite wavevector regime the dynamic correlations are completely determined by a single free motion of the molecules.